KWH METER IMAGE ENHANCEMENT USING COLOR SPACE TRANSFORMATION FOR IMPROVING CHARACTER SEGMENTATION ACCURACY - Shinta Puspasari; Lastri Widya Astuti (Jurnal Ilmiah Kursor, 2016)
This study proposes an approach to enhance image quality of power meter (KWH meter) using a color space transformation. Power meter is used to measure the power consumption of the customer. The amount of usage can be seen by looking at the character of numbers as indicators of measurement. Billing can be done automatically using character recognizer on imaging device by applying digital image processing techniques. Acquired image of the power meter may have poor quality because data acquisition process is very sensitive to light and noise. Appliance power meter is covered with glass that can reflect light, so that the quality of the acquired image varies depends on the lighting conditions at the time of acquisition. Color space transformation widen the color contrast of KWH meter image. The performance of the proposed approach is evaluated using a data set of KWH meter images of Smart Meter Indonesia models contains 30 RGB color model images. Before performs the proposed method, segmentation effectivesess is 93%. The experimental results shows an improvement of image quality that affect the character segmentation results up to 97%. Color space transformation is proven effective for the improvement of image quality and segmentation of KWH meter.